FORMULASI DETERJEN RAMAH LINGKUNGAN DENGAN SERBUK SIMPLISIA DAUN WARU (Hibiscus tilliaceus L.) DAN BUAH LERAK (Sapindus rarak DC.) SEBAGAI SURFAKTAN - Nurrosyidah, Iif Hanifa; Putri, Erica Novia; Satria, Berlian Adi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
The purpose of this study was to develop an environmentally friendly detergent formula containing simplicial powder of hibiscus leaf (Hisbiscus tiliaceus L.) and lerak fruit (Sapindus rerak DC.) and combined with biodegradable surfactants (Decyl Glucoside and Lauryl Glucoside) so that they are easy to biodegrade. The research method includes making liquid detergent using three formulas, namely F I, F II, and F III with variations in the concentration of hibiscus leaf and lerak fruit simplicial powder used. Physical characteristic test of liquid detergent according to the quality requirements of SNI SNI 06-4075-1996 includes organoleptic, pH, foam stability test, and contamination analysis by determining the total plate number (ALT). Based on the results of this study, the three detergent formulas have physical characteristics according to the quality requirements of SNI